Advancing pharmacotherapy for diabetic foot ulcers. (13th June 2019) - Eleftheriadou, Ioanna; Tentolouris, Anastasios; Tentolouris, Nikolaos; Papanas, Nikolaos
ABSTRACT: Introduction : Standard treatment for diabetic foot ulcers (DFUs) includes off-loading, debridement, moisture balance, management of infection and peripheral arterial disease (PAD) as well as adequate glycemic control. The outcomes so far are unsatisfactory. Areas covered : Herein, the authors provide an outline of newer pharmacological agents for the management of DFUs and give their expert perspectives on future treatment strategies. Expert opinion : Evidence-based healthcare calls for high quality evidence from large RCTs before the implementation of new guidelines for the management of DFUs. Empagliflozin and liraglutide can be recommended for glucose control in patients with DFUs and PAD, while intensive lipid lowering therapy with evolocumab when primary cholesterol goals are not met could be offered to patients with DFUs. Further clinical studies are warranted to develop a structured algorithm for the treatment of DFUs that fail to heal after four weeks of current standard of care. Sucrose octasulfate dressings, becaplermin gel, and platelet-rich plasma (PRP) could also be considered as advanced treatment options for the management of hard to heal DFUs.